Written Differently: A Survey of Commonwealth Constitutional History in the Age of Decolonisation. Issue 5 (3rd September 2018) - Kumarasingham, H.
ABSTRACT: This article provides a survey and definition of the field of Commonwealth constitutional history since 1918, especially during and after global decolonisation. It asks what is Commonwealth constitutional history and how it differs from its English and Imperial counterparts. The article puts forward a working definition of Commonwealth constitutional history and introduces key and diverse writers who illustrate the range and potential of this history. The article provides an historiography and survey of constitutional history in the Pre-Commonwealth and Post-war Commonwealth periods while also assessing the opportunities of Post-British Commonwealth constitutional history. The objective of this article is to show how Commonwealth constitutional history can contribute to the historical study of state power and to see its worth to other disciplines and fields of history. Commonwealth constitutional history is a necessity to examine the politics, power and consequences of the British empire during the long age of decolonisation.